Implementing a First-Year Experience Curriculum in a Large Lecture Course: Opportunities, Challenges and Myths - Ahadi, Daniel; Pedri, Jennesia; Nichols, L. Dugan (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
This article documents the design, delivery, and evaluation of a first-year experience (FYE) course in media and communication studies. It was decided that CMNS 110: Introduction to Communication Studies would start to include elements to address a perceived and documented sense of disconnectedness among first-year students in the School of Communication at Simon Fraser University. These elements included coping, learning, and writing workshops facilitated by various services units across campus. We present results from surveys and focus groups conducted with students at the end of the course and discuss the predicaments that the new realities of an accreditation and audit paradigm—under the cloak of the neoliberal university—produce. On one hand the FYE course may help students transition into a post-secondary institution; on the other hand, too much emphasis on the FYE can result in an instrumental approach to education, jeopardizing the integrity of the course. We offer some insights into the challenges and opportunities of implementing FYE curricula within a large classroom setting.